(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
This paper deals with the stratigraphy of well SPAN 1 (San Pietro al Natisone, Eastern Friuli). The stratigraphic sequence is composed by Paleocenic flysch deposits (from 69 m to 748 m), Maastrichtian resedimented carbonates (from 748 m to 940 m) and Late Jurassic reef deposits (from 940 m to 1397 m, total depth). The tectonic and sedimentary evolution of the Valle del Natisone, from the Oxfordian to the Early Eocene, is outlined.